Morphogenesis of Canine Chiari Malformation and Secondary Syringomyelia: Disorders of Cerebrospinal Fluid Circulation - Knowler, Susan P.; Galea, Gabriel L.; Rusbridge, Clare (Frontiers in Veterinary Science, 2018)
Chiari-like Malformation (CM) and secondary syringomyelia (SM), as well as their analogous human conditions, is a complex developmental condition associated with pain and accompanying welfare concerns. CM/SM is diagnosed ever more frequently, thanks in part to the increased availability of magnetic resonance imaging in veterinary medicine. Research over the last two decades has focused primarily on its pathophysiology relating to overcrowding of the cranial caudal fossa. More recent characterisations of CM/SM include brachycephaly with osseous reduction and neural parenchymal displacement involving the entire brain and craniocervical junction to include rostral flattening, olfactory bulb rotation, increased height of the cranium, reduced cranial base with spheno-occipital synchondrosis angulation, reduced supraoccipital and interparietal crest and rostral displacement of the axis and atlas with increased odontoid angulation. The most shared manifestation of CM is the development of fluid-filled pockets (syrinx, syringes) in the spinal cord that can be readily quantified. Dogs with symptomatic CM without SM have a reduced basioccipital bone, compensatory increased cranial fossa height with displaced parenchyma whereby the cerebellum is invaginated beneath the occipital lobes but without compromising cerebrospinal fluid channels enough to cause SM. Thus, broadly defined, CM might be described as any distortion of the skull and craniocervical junction which compromises the neural parenchyma and cerebrospinal fluid circulation causing pain and/or SM. The aetiology of CM is multifactorial, potentially including genetically-influenced, breed-specific abnormalities in both skeletal and neural components. Since causation between specific morphologic changes and SM or clinical signs is unproven, CM might be more appropriately considered as a brachycephalic obstructive CSF channel syndrome (BOCCS) rather than a single malformation. Understanding the normal development of the brain, skull and craniocervical junction is fundamental to identifying deviations which predispose to CM/SM. Here we review its anatomical, embryological, bio-mechanical, and genetic underpinnings to update the profession’s understanding of this condition and meaningfully inform future research to diminish its welfare impact.